Changes in biochemical and antioxidant enzymes activities play significant role in drought tolerance in soybean - Mishra, N.; Tripathi, M. K.; Tripathi, N.; Tiwari, S.; Gupta, N.; Sharma, A.; Shrivastav, M. K. (International Journal of Agricultural Technology, 2021)
Soybean genotypes were grouped into two clusters on the basis of biochemical profiling, anti-oxidant enzyme activities and protein profiling. Biochemical and antioxidant enzyme activity analysis among 53 genotypes revealed the presence of drought tolerance traits in three genotypes viz., JS97-52, RVS-14 and JS95-60. The result obtained may contribute towards improvement of soybean genotypes with the development of drought tolerant varieties with the applications of conventional as well as molecular breeding approaches. These findings also provided a base for further research to investigate the drought tolerance mechanism in soybean crop using advanced biotechnological tools